Оптимізація розмірів балкових елементів рами трактора в середовищі matlab: аналітичний, чисельний та робастний підходи для суцільних і порожнистих перерізів - Одновол, Дмитро Геннадійович; Дяденчук, Альона Федорівна; Odnovol, Dmytro; Diadenchuk, Alona (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: У статті розглянуто аналітичний, чисельний та робастний підходи до оптимізації розмірів балкових елементів рами трактора з використанням середовища MATLAB. Побудовано математичну модель мінімізації маси балки за умов обмежень на міцність і жорсткість, що формулюється як задача нелінійного програмування з двома змінними (ширина і висота перерізу). Для базового випадку отримано аналітичний розв’язок, який узгоджується з результатами чисельної мінімізації методом послідовного квадратичного програмування. Проведено параметричний аналіз впливу граничного прогину та навантаження на оптимальні геометричні характеристики, досліджено робастність розв’язку при випадкових відхиленнях сили ±20 %, а також порівняно суцільні й порожнисті перерізи. Показано, що порожнистий профіль забезпечує зменшення маси до 25 % без порушення вимог до міцності та жорсткості. Додатково виконано оцінку втомної довговічності за критеріями Гудмана-Содерберга та визначено запас стійкості балки до крутильно-вигинного викривлення. Отримані результати підтверджують ефективність використання MATLAB для конструкційної оптимізації елементів рам тракторів та підвищення їх енергоефективності. /// EN: This study presents an integrated analytical, numerical, and robust optimization framework for determining the optimal geometric dimensions of tractor frame beam elements within the MATLAB computational environment. The problem is formulated as a nonlinear programming (NLP) task aimed at minimizing beam mass under dual constraints of strength and stiffness, expressed via maximum bending stress and allowable deflection limits. The analytical solution, derived from Euler–Bernoulli beam theory, was validated using the Sequential Quadratic Programming (SQP) algorithm implemented through MATLAB’s fmincon function, demonstrating excellent convergence and consistency between analytical and numerical results. A series of parametric and sensitivity analyses were conducted to evaluate the influence of allowable deflection, external load magnitude, and geometric bounds on the optimal beam dimensions. The results indicate that stiffness constraints dominate mass minimization, and tightening the deflection limit leads to a nonlinear increase in beam height and overall weight. Robust optimization was performed using the Monte Carlo simulation method to account for stochastic variations in load and material properties (±20 %). It was found that achieving 95 % reliability requires approximately a 20 % increase in beam width, resulting in a comparable rise in mass. Additionally, solid rectangular sections were compared with hollow rectangular (RHS) profiles, demonstrating that the latter can achieve a 20–25 % reduction in mass while maintaining equivalent stress and deflection levels. Fatigue verification based on the Goodman–Soderberg criteria confirmed that the optimized beam design ensures sufficient endurance under variable cyclic loading. A lateral-torsional buckling (LTB) check revealed that the critical bending moment exceeds the applied moment by more than an order of magnitude, ensuring global stability. The proposed methodology offers a unified MATLAB-based approach that integrates analytical modeling, numerical optimization, and probabilistic robustness assessment. It serves as a practical decision-support tool for engineers engaged in designing lightweight and durable structural components of agricultural machinery and tractor frames, contributing to energy efficiency and material savings in modern agro-industrial engineering.
Optimization of tractor frame beam dimensions in matlab environment: analytical, numerical, and robust approaches for solid and hollow cross-sections
Keywords: оптимізація конструкцій; MATLAB; нелінійне програмування; міцність і жорсткість; робастна оптимізація; втомна довговічність; стійкість балки; рамна конструкція трактора; порожнистий про¬філь; метод скінченних елементів; structural optimization; nonlinear programming; strength and stiffness; robust optimization; fatigue durability; beam stability; tractor frame structure; hollow profile; finite element method